Effect of CRP and Kinetics of CRP in Prognosis of Nasopharyngeal Carcinoma - Chen, Ruiwan; Zhou, Yu; Yuan, Yujie; Zhang, Qun; He, Shasha; Chen, Yong; Ren, Yufeng (Frontiers in Oncology, 2019)
Baseline C-reactive protein (CRP) has been determined as a prognostic factor in nasopharyngeal carcinoma (NPC). This study was designed to further evaluate the impact of CRP kinetics on NPC patients. Thousand three hundred and seventy eight NPC patients from February 2001 to June 2011 were retrospectively reviewed. CRP were measured at beginning, middle, and the end of the treatment. The endpoints were overall survival (OS) and distant metastasis free survival (DMFS). Patients were divided into three groups according to baseline CRP and CRP kinetics: (1) continuously normal group: patients whose baseline CRP normal and never elevated, (2) ever-elevated group: patients whose CRP ever elevated regardless time points, (3) continuously elevated group: patients whose baseline CRP elevated and never normalized. Baseline CRP, CRP after treatment, and CRP kinetics were correlated with TNM stage, T stage, and N stage. Univariate and multivariate analysis identified that elevated baseline CRP and CRP after treatment had significant association with worse survival than normal CRP. Oppositely, elevated CRP during treatment was not associated with survival. Patients with continuously elevated CRP significantly had poor OS and DMFS (HR:2.610, 95%CI: 1.592–4.279, p < 0.001; HR:2.816, 95%CI: 1.486–5.302, p = 0.001, respectively). In multivariate analysis, CRP kinetics assessment is an independent prognostic factor for OS and DFMS in NPC patients (HR:2.512, 95%CI: 1.452–4.346, p = 0.001; HR:3.389, 95%CI: 1.734–6.625, p = 0.001, respectively). In conclusion, elevated CRP at baseline and after treatment are predictive factors of poor prognosis for NPC. The study of CRP kinetics shows that continuously elevated CRP during treatment might indicate an unfavorable prognosis for NPC.